Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/all.12466
|View full text |Cite
|
Sign up to set email alerts
|

Standardized testing with chlorhexidine in perioperative allergy – a large single‐centre evaluation

Abstract: In patients investigated for suspected perioperative allergic reactions, 9.6% were diagnosed with allergy to chlorhexidine. Using our definition of chlorhexidine allergy, the highest combined estimated sensitivity and specificity was found for specific IgE and SPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
136
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(142 citation statements)
references
References 30 publications
2
136
0
1
Order By: Relevance
“…Significant geographical differences are reported concerning the incidence of chlorhexidine-perioperative induced anaphylaxis. Reactions are quite frequent in UK and Scandinavian countries [71,103,104], representing the 8.7%-9.6% of cause inducing perioperative anaphylaxis but relatively rare in France [22] perhaps because of its limited use in the operating room. The mechanism is IgE mediated and although reactions usually appear 20-30 minutes after its administration, onset and severity depend on the administration route, with cutaneous application rarely causing severe reaction [36].…”
Section: C) Antiseptics and Sterilizersmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant geographical differences are reported concerning the incidence of chlorhexidine-perioperative induced anaphylaxis. Reactions are quite frequent in UK and Scandinavian countries [71,103,104], representing the 8.7%-9.6% of cause inducing perioperative anaphylaxis but relatively rare in France [22] perhaps because of its limited use in the operating room. The mechanism is IgE mediated and although reactions usually appear 20-30 minutes after its administration, onset and severity depend on the administration route, with cutaneous application rarely causing severe reaction [36].…”
Section: C) Antiseptics and Sterilizersmentioning
confidence: 99%
“…Skin prick tests with latex also show a high sensitivity and specificity (grade of recommendation, B) (93% and 100%, respectively) [122]. Clorhexidine also has a high sensitivity and specificity: 95% and 97% respectively for skin prick tests and 68% to 100% for intradermal tests (grade of recommendation, B) [103].…”
Section: Skin Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorhexidine is an increasingly recognized cause of anaphylaxis. Although the actual incidence of anaphylaxis regarding this agent is unknown, a study of patients that had had perioperative anaphylaxis revealed that 9.6% of them had a positive skin test to chlorhexidine [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Because of highly efficient avoidance strategies, the prevalence of anaphylaxis to latex declined during the last years and is now considerably less than would be suggested by the presence of specific IgE (sIgE) or positive skin tests (6). Instead, increasingly other elicitors of anaphylaxis have been reported in the perioperative setting (2,7,8).…”
mentioning
confidence: 99%